Predictors of exclusive breastfeeding in Roma and non-Roma population in Serbia. (30th September 2020) - Stamenković, Ž; Bjegovic-Mikanovic, V; Matejic, B; Djikanovic, B
Abstract: Background: Exclusive breastfeeding is essential for early childhood development, although the use of adaptive milk formulas instead of breastfeeding is widespread nowadays. This study examined the prevalence of exclusively breastfed infants under the age of 6 months in non-Roma and Roma population and factors associated with this practice. Material and Methods: This study is a secondary analysis of the Serbian Multiple Indicator Cluster Survey investigating non-Roma and Roma infants under the age of 6 months. The study included mothers of 321 non-Roma and 164 Roma infants younger than 6 months. Univariate and multivariate logistic regression served to analyze factors associated with the practice of exclusive breastfeeding. Results: The prevalence of exclusive breastfeeding was almost the same among mothers in both non-Roma and Roma population (13.3% vs. 13%). Exclusive breastfeeding was significantly more often (p < 0.001) among wealthier women, multipara, and women who had not established menstrual cycle among both populations. Unexpectedly, in the non-Roma population, not staying in the same room with the newborn in the maternity ward increases the chance for the baby to be exclusively breastfed (OR 7.19, CI 95% 1.80-28.68). The same pattern has been observed in Roma population. Non-Roma mothers multipara are more likely to exclusively breastfeed their children than primipara (OR 7.78, CI 95% 1.09-20.93), while among Roma mothers, the inverse association has been found although not significant. Attending a childbirth preparation program more than 18 times increases the chances of infants being exclusively breastfed (OR 18.65, CI 95% 1.34-53.67). In the Roma population, there was no single woman that attended a childbirth preparation program. Conclusions: The pattern of exclusive breastfeeding significantly differs between non-Roma and Roma populations. Preventive work should have a focus on strengthening support to mothers and medical staff in maternity wards. Key messages: Understanding the predictors of exclusive breastfeeding can help in the process of creating health promotion programs that lead to more infants exclusively breastfed according to the WHO guidelines. Decision-makers and public health authorities should acknowledge the existing breastfeeding problems.